2002
DOI: 10.1677/joe.0.1730187
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic regulation of catecholamine secretion from trout (Oncorhynchus mykiss) chromaffin cells

Abstract: The interaction between extracellular catecholamines and catecholamine secretion from chromaffin cells was assessed in rainbow trout (Oncorhynchus mykiss) using an in situ saline-perfused posterior cardinal vein preparation. This was accomplished by comparing the effects of adrenergic receptor agonists and antagonists on stimulus-evoked secretion. An acute bolus injection or extended perfusion with saline containing high levels of either noradrenaline or adrenaline did not affect the baseline secretion of cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…It functions as a physiological modulator of CA secretion by non-competitively suppressing ACh-induced cytosolic Ca 2+ dynamics in bovine adrenal chromaffin cells (Suzuki et al, 1999). And also there had a feedback inhibition of CA secretion by activating chromaffin cell membrane beta (2) -receptors and presynaptic alpha (2) -adrenergic receptors (Montpetit and Perry, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It functions as a physiological modulator of CA secretion by non-competitively suppressing ACh-induced cytosolic Ca 2+ dynamics in bovine adrenal chromaffin cells (Suzuki et al, 1999). And also there had a feedback inhibition of CA secretion by activating chromaffin cell membrane beta (2) -receptors and presynaptic alpha (2) -adrenergic receptors (Montpetit and Perry, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic study revealed which function of the carp immune system was most affected by hypoxic stress and how the duration of stress influences the expression of these functions. Acute stress enhances the fast pathway that activates the sympathetic nervous system to release catecholamines, such as adrenaline and noradrenaline, from chromaffin cells in the head kidney, and the released catecholamines bind to their receptors in leucocytes [ 101 , 102 ]. As a result, the proinflammatory function (IL‐1b, IL‐6 and tumour necrotic factor α (TNFa)) is upregulated and, at the same time, the activity of regulatory function (TGFb and IL‐10) is upregulated, probably in order to return proinflammatory activity to homeostasis [ 100 , 103 ].…”
Section: Influence Of Stress On the Immune Systemmentioning
confidence: 99%
“…In a study on β‐adrenergic effects on insulin signaling in adipocytes from β 3 ‐adrenoceptor “knock‐out mice”, dobutamine was used as “the classical β 1 ‐adrenoceptor agonist” (Jost et al 2002). Furthermore, dobutamine was employed to investigate the mechanism of adrenergic inhibition of catecholamine secretion from trout cromaffin cells in vitro (Montpepit & Perry 2002) and to test “the hypothesis that nitric oxide has a positive inotropic effect on mammalian cardiac muscle contractility and that this effect sums with the positive inotropic effect of β 1 ‐adrenergic agonists when both are present” (Reading & Barclay 2002). None of these authors appear to have considered the chiral nature of dobutamine.…”
Section: Classical Delusionsmentioning
confidence: 99%